2019
DOI: 10.4103/jets.jets_123_18
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid versus nonsubarachnoid traumatic brain injuries: The impact of decision-making on patient safety

Abstract: Introduction:Traumatic intracranial hemorrhages (ICHs) are high priority injuries. Traumatic brain bleeds can be categorized as traumatic subarachnoid hemorrhage (SAH) versus non-SAH-ICH. Non-SAH-ICH includes subdural, epidural, and intraventricular hematomas and brain contusions. We hypothesize that awake patients with SAH will have lower mortality and needless interventions than awake patients with non-SAH-ICHs.Study Design and Methods:A review of data collected from our Level I trauma center was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A retrospective cohort study comparing 225 iTSAH patients and 826 non-SAH-ICH patients found that 0.89% (n=2) tSAH patients and 12.1% (n=100) of non-SAH-ICH patients required neurosurgical intervention. 14 Mortality rates were 1.78% (n=4/225) in the SAH patients and 2.66% (n=22/826) in the non-SAH-ICH patients.…”
Section: Resultsmentioning
confidence: 89%
“…A retrospective cohort study comparing 225 iTSAH patients and 826 non-SAH-ICH patients found that 0.89% (n=2) tSAH patients and 12.1% (n=100) of non-SAH-ICH patients required neurosurgical intervention. 14 Mortality rates were 1.78% (n=4/225) in the SAH patients and 2.66% (n=22/826) in the non-SAH-ICH patients.…”
Section: Resultsmentioning
confidence: 89%
“…Compared to Group I patients, there were significantly more patients in Group III who had HTN and DM. The group of patients with isolated traumatic SAH had a significantly higher GCS score (median [Q1–Q3]: 15 [14,15]) than the other three groups (Group II: 14 [10,11,12,13,14,15], Group III: 13 [7,8,9,10,11,12,13,14,15], and Group IV: 8 [4,5,6,7,8,9,10,11,12,13,14]), as well as a smaller percentage of patients with a GCS score of ≤ 8 and a greater percentage of patients with a GCS score of ≥13. In addition, the group of patients with isolated traumatic SAH had a significantly lower ISS (median [Q1–Q3]: 11 [9,10,11,12,13,14]) than the other three groups (Group II: 16 [16,17,18,19,20], Group III: 17 [16,17,18,19,20,21,22,23,24], and Group IV: 21 [16,17,18,19,20,21,22,23,24,25]) and presented with a greater percentage of patients with a ISS of <16 and a smaller percentage of patients with a ISS between 16–24 and ≥25.…”
Section: Resultsmentioning
confidence: 99%
“…The actual death rate and the requirement for neurosurgical intervention in SAH cases is significantly lower than in cases of non-SAH intracranial hemorrhages [8]. In addition, the outcome is good for patients with isolated traumatic SAH, which is defined as the exclusive presence of SAH without any other traumatic, radiographic intracranial pathology in the trauma patient.…”
Section: Introductionmentioning
confidence: 99%
“…Subarachnoid haemorrhage (SAH) refers to the accumulation of blood within the subarachnoid space. The aetiology of SAH can be broadly classified into 2 categories: traumatic SAH and non-traumatic or spontaneous SAH [ 1 ]. Traumatic SAH, which frequently occurs after head trauma, is typically a benign condition that exhibits a favourable prognosis, rarely necessitating surgical intervention [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology of SAH can be broadly classified into 2 categories: traumatic SAH and non-traumatic or spontaneous SAH [ 1 ]. Traumatic SAH, which frequently occurs after head trauma, is typically a benign condition that exhibits a favourable prognosis, rarely necessitating surgical intervention [ 1 ]. Unlike spontaneous SAH, which has the risk of a life-threatening condition.…”
Section: Introductionmentioning
confidence: 99%